Editorial. Issue 1 (1st March 2017) - Wilkinson, Nicholas
Abstract : VR is a new term to me. With a couple of words in brackets immediately after the abbreviation, (Virtual Reality) all is clear and well. Thank you to a colleague of mine. (See manuscript title CREATIVITY IN THE INITIAL PHASES OF ARCHIECTURAL DESIGN. Page 29 On the same level use of the abbreviation CD is more well known than the use of its actual meaning of Compact Disc.